SCHOOL PHYSICAL EDUCATION AND HEALTH: AN EXPERIENCE INTERDISCIPLINARY IN EARLY GRADES OF THE ELEMENTARY SCHOOL (Fiep Bulletin - online, 2012)
This work deals with the health issue from the school Physical Education, which has as content its insertion in cross-cutting issues in an interdisciplinary project linked with the discipline Sciences in the early grades of Elementary School I. Its aim is to identify relationships between the contents of interdisciplinary health focused on discipline Sciences and Physical Education, seeking to present knowledge for the early grades of Elementary School, from the transversal theme of health. In this paper will be focused on number-3 specific objective of this study: to develop laboratory classes in physical education classes in the 2nd to 5th grade of Elementary School with interdisciplinary content on health, from the books of Science in these classes. It was chosen the descriptive research within a qualitative perspective, and the surveyed group composed of four science teachers from the 2nd to 5th grade and two of physical education of Elementary Education at a private school in the city of Natal-RN. Besides, three groups to experience the school laboratories. The instruments used to meet the number-3 goal focused in this article are: reading and analysis of books used in the classroom by teachers of science these grades and three lab-lesson plans experienced in groups of 2nd, 3rd and 5th grades of school. It is thus realized that with the base already seen in the Science discipline associated with experience in physical education was possible to see a new knowledge by relating physical activity to health from an interdisciplinary perspective. Raising awareness of student, about the relationship between health and bodily practices during the school could provide important contributions to the consolidation of healthy habits in the current and future students.
Keywords: School Physical Education; Health; Interdisciplinary